Prevalence of Parasites and Water Quality Measurement in Vannamei Shrimp (Litopenaeus vannamei) Ponds in Padang Pariaman Area, Indonesia - Mairawita Mairawita; Taufik Rahman; Fajri Hidayat (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: The vannamei shrimp (Litopenaeus vannamei Boone) is a marine species of high economic value. Meanwhile, vannamei shrimps are easily attacked by parasites that can cause failure in the cultivation. This study aims to investigate ectoparasites and endoparasites in vannamei shrimp ponds in the Padang Pariaman area in terms of their prevalence and the pond water quality. Methodology: This research was carried out by purposive random sampling method. The parasites identification were conducted at the Animal Taxonomy Laboratory, Biology Department, Universitas Andalas. Findings: Six species of ectoparasites were found, namely Acineta sp., Arcella sp., Epistylis sp., Trichodina sp., Vorticella sp., and Zoothamnium sp. Moreover, only one species of endoparasite was found, namely Enterocytozoon hepatopenaei (EHP). The prevalence of ectoparasite species was highest in Zoothamnium sp. in 40-day-old shrimp (80 %) and 63.3 % in 30-day-old shrimp. Further, the prevalence of endoparasites was highest in female shrimp (94.5 %), while it was 87.8 % in male shrimp. Furthermore, there were six parameters of shrimp pond water quality that do not meet the cultivation standards, namely pH, DO, BOD, COD, ammonia, and zinc, while the other two parameters meet the standards, namely temperature and salinity. In conclusion, the production of vannamei shrimp can be reduced and parasitic disease outbreaks can result from water quality that does not meet culture standards. Contribution:This study contribute to the shrimp ponds in the area in managing stocking density, feeding levels, and sanitation.